Pharmacokinetics of esomeprazole in goats (Capra aegagrus hircus) after intravenous and subcutaneous administration - Fladung, Rachel; Smith, Joe S.; Hines, Melissa T.; Soto-Gonzalez, Windy Michelle; Fayne, Bryanna; Rahn, Rebecca R.; Escher, Olivia Grace; Harvill, Lainey; Bergman, Joan; Garcia, Jessica D.; Kreuder, Amanda Jo; Cox, Sherry (Frontiers in Veterinary Science, 2022)
Background: Stressed and hospitalized goats are at risk abomasal (gastric) ulceration, but there is a paucity of pharmacokinetic studies for proton pump inhibiting drugs, such as, esomeprazole in goats. Objectives: The objectives for this study were to estimate plasma pharmacokinetic parameters for esomeprazole in adult goats after intravenous (IV) and subcutaneous (SQ) administration. A secondary objective was to describe the plasma kinetics of the metabolite esomeprazole sulfone after IV and SC administration in goats. Materials and Methods: Esomeprazole was administered to 5 adult goats in a crossover study at doses of 1 mg/kg IV or 2 mg/kg SC. Plasma samples were collected over 36 h and analyzed via reverse phase HPLC to determine concentrations of esomeprazole and esomeprazole sulfone. Pharmacokinetic parameters were derived via non-compartmental analysis. Results: Following IV administration, mean values for plasma clearance (Cl), elimination half-life [T1/2 (λz)] , C0, and volume of distribution (Vz) of esomeprazole were estimated at 24.9 mL/min/kg, 6 min, 2.324 μg/mL, and 0.23 L/kg, respectively. After SC administration elimination half-life, maximum concentration (Cmax) and time to maximum concentration (Tmax) of esomeprazole were estimated at 29 min, 1.038 μg/mL, and 22 minutes respectively. Maximum concentrations of the sulfone metabolite were 32 and 18 ng/mL after IV and SC administration. Conclusion: Esomeprazole was rapidly eliminated from plasma after both IV and SC injection in goats. The elimination half-life in goats appears to be shorter than reported in dogs, as well as less than that reported for pantoprazole in goats. The sulfone metabolite was detected and also rapidly eliminated from the plasma after both IV and SC administration. Additional pharmacodynamic investigations are needed to determine the efficacy of esomeprazole on abomasal (gastric) acid suppression in goats and could include larger doses or additional routes of administration.